La pace perpetua a due voci: Kant e Cusano - Ricci Sindoni, Paola (B@belonline, 2024)
Both Cusano and Kant speak of “perpetual peace”, both undertake to write an essay on the theme of peace: Cusano in 1453 with De pace fidei and Kant in 1795 with perpetual peace. But that’s not all: both Cusano and Kant explicitly address the question of peace not as an ethical, political or diplomatic program aimed at putting an end to a conflict, but as a theoretical vision placed as a presupposition for any application on the level of political and religious praxis. Almost as if to say that only in times of peace must peace be produced, as Psalm 34:15 also says: «If you want peace, seek it, run after it, pursue it», and that this assumption makes peace a true and proper methodological principle, founded for both on an ontological thesis, that is, that of a fundamental “concordance” of all human beings, on the level of reason and justice and on the evidence of the opposition between unity and multiplicity.